"I believe in a god that I believe in" : the religious identity of primary school student teachers - Sheridan, John-Paul (Trinity College (Dublin, Ireland). School of Education, 2012)
This research is a case study which sought to explore and map the religious identity of a group of thirty primary school student teachers in their third and fourth year of teacher education. The questions arose because of my personal experience of primary school teachers over the last twenty years in schools under religious patronage, where there is a requirement to teach religious education. The study was framed in the social, political and economic landscape of Ireland from 1990 – 2010, which broadly encompasses the life-span of these students. The country witnessed great socio-economic change: the rise of a vibrant economy and industrial stability; the arrival of immigrants from all over the world; the building boom and the rise of a consumerism not seen in Ireland before. There was a changing political landscape: the election of two female Presidents of Ireland; political stability; and the success of the Northern Ireland Agreement. As well as this secular change, it was a period of religious change, when religious affiliation and attendance at religious services continued to decline. It was also a period which saw the failures of the Catholic Church uncovered and laid out in public. Religious Congregations and Dioceses were investigated by Government Inquiries as the sexual, physical and psychological abuse of children was exposed. The aim of the literature review is to survey identity theory in a number of different ways. It is divided into three sections to investigate identity theory, teacher identity and religious identity. The identity theory is also divided into three sections to review social identity, personal identity and self-concept. The section on teacher identity is concerned with emerging or beginning teacher identity and how teachers begin to negotiate their role as teachers and the concept of professionalism. In both general identity and teacher identity a number of concepts emerge – identity is seen both as an internal and an external entity: how a person reconciles internally one’s identity and how a person’s identity comes across to the people one encounters. In a similar manner, identity is both personal and social - as much about a person on their own, as it is about them as part of a group. Another common concept is narrative identity is interpreted through the story of a teacher’s life: their experiences and how they learn from them; their mistakes and how they correct them; their aspirations and how they attain them. The religious identity section is divided into two parts – public religion and religious identity. The public religion looks at secularization theory and the situation of religion in Ireland as might be experienced by student teachers. The section on religious identity looks as how this identity is manifest in the individual, in particular with the concept of spiritual versus religious. This separation of one from the other is increasingly prevalent, which makes for the separation of individual spiritual life from mainstream religious denomination. A final component of the identity section is the chapter on the writings of Karl Rahner. As the primary function of the study is to investigate and map the religious identity of primary school student teachers, Rahner’s writings are used to provide a more comprehensive identity - a thick description. Three elements are explored – his Theological Anthropology; his Epistemology; and his Pastoral Theology. Rahner’s writing echoes a great deal of what is said here about identity theory, teacher identity theory and obviously religious identity theory, but it gives it a final dimension - he orientation towards God. This orientation is not just in terms of who we are as people, but also how we understand and make meaning of that identity. The literature review and chapter on Rahner are then framed theoretically so as to give a comprehensive basis for creating the interrogative stage and writing the research questions. There are three questions: What characterises the religious identity of a Primary School Student Teacher? How does a Primary School Teacher understand their Religious Identity? How does their religious identity influence their teaching religion in Primary Schools? The first two questions are answered by the thick description - the rich, comprehensive description of the religious identity of the student teachers and how they understand that identity. The third question will be answered by exploring the student teachers’ initial experience of teaching and teaching religion. The general research paradigm is social constructivism/ interpretivism; a paradigm which is concerned with the way that individuals interpret their world. Part of this interpretation will include the use of narrative and phenomenology as methods. The principal at the heart of the work is the ‘double hermeneutic’ - my interpretation of their interpretation. This is a case study of thirty students, bounded geographically, chronologically, and demographically. The case study offers both a unity of purpose, a sufficient depth of study, and an expansive level of description to meet the purposes of the research. All five colleges of Education in the Republic of Ireland were approached; one declined to be involved, one was uncooperative and the remaining three allowed me to interview some of their third-year students. I met with the students in each college as a group and invited them to participate. I also spoke to a number of fourth-year students and eight of these were willing to be interviewed. A semi-structured interview method was used with the thirty students with all considerations of ethics, confidentiality and anonymity duly noted and attended to. The interviews were transcribed by a team of typists. The data generation and collation was undertaken manually. Codes were applied to the interview transcripts and these were gathered in to sets of codes, themes and concepts. The explanation and exposition of the themes and concepts was then completed. This exploration of the data is divided into five sections, along the same lines as the literature review and the research questions: identity theory; teacher identity; religious identity; understanding religious identity; and teaching and religion. The eighth chapter returns to the three research questions. The first two research questions regarding religious identity and the student’s understanding of it encompass the ‘thick description’ outlined in chapter seven. This description of the three modes of identity is outlined in the literature review and used at the interrogative stage is enriched by Rahner’s anthropology and it provides the basis for four typologies of religious identity which are employed to create an image of the student teachers who were interviewed. The third research question lays out the findings concerning religious identity and teaching religion and takes into consideration the current debate concerning school patronage and management and the religious education background of the student teachers. The final chapter is a summative chapter and as well as outlining some of the limitation of the study, provides the research findings in a summative form along with major recommendations and areas of further research.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin